Tristan Corbière Oysters, nightingales and cooking pots - Corbière, Tristan (White Rose University Press, 2018)
Tristan Corbière is a poet who tests language to the limits, dislocating normal syntax, revelling in self-contradictory affirmations, and piling up puns. Born in Brittany in 1845, he died at only 29, leaving to future readers a scattered assortment of texts. This collection brings together several less well-known pieces, some early versions of published poems, and others which were handwritten into his own copy of his only published collection, Les Amours jaunes. Presented as a bilingual edition, this volume offers the first English translations of many of these writings, all of which testify to Corbière's sly humour, linguistic glee, formal innovation and mordant self-irony. Playful and comic, Corbière's work is also experimental, subversive and moving. The texts are translated by Christopher Pilling, an award-winning poet, playwright and translator. He is a founder of the Cumbrian Poets workshops, which he has hosted for 35 years, a convenor of Skiddaw u3a, and the organiser of translation days and readings in Keswick. He has translated the work of a number of poets, mainly from French but also from Latin. A beneficiary of the Royal Literary Fund, Christopher is also a member of Parkinson's UK. Oysters, nightingales and cooking pots provides a fitting sequel to Christopher Pilling's translation of Tristan Corbière's Les Amours jaunes, published as These Jaundiced Loves in 1995. The volume is edited by Richard Hibbitt and Katherine Lunn-Rockliffe.